Artistic Characteristics in the Works of Riqqat Qunt (The International Journal of Educational Sciences and Arts, 2025)
This study investigates the artistic characteristics in the works of the ornament designer Riqqat Qunt .The research problem is framed around a central question: What are the defining artistic characteristics in the works of Riqqat Qunt?The primary aim is to examine the most prominent artistic features in her creations within the field of Islamic ornamentation, with a focus on identifying the technical attributes of the compositional systems and formal structures employed in her decorative practice. The findings are anticipated to offer valuable insights for ornament designers, calligraphers, and scholars of Arabic calligraphy and Islamic decorative arts.The theoretical framework addresses several key themes: the essence of decorative art; the conceptual design approach in constructing ornamental compositions; the diversity of techniques and materials evident in Qunt body of work; and the formal organizational strategies she applies in the execution of her designs.Methodologically, the study adopts a descriptive–analytical approach, examining a research population of (20) works produced by Qunt across a range of materials. From this population, (2) purposively selected samples were analyzed in detail.
Keywords: Artistic Characteristics; Decoration; Riqqat Qunt